Pug-Headedness Anomaly in a Wild and Isolated Population of Native Mediterranean Trout Salmo trutta L., 1758 Complex (Osteichthyes: Salmonidae) - Palmas, Francesco; Righi, Tommaso; Musu, Alessio; Frongia, Cheoma; Podda, Cinzia; Serra, Melissa; Splendiani, Andrea; Caputo Barucchi, Vincenzo; Sabatini, Andrea (Diversity (Basel), 2020)
Skeletal anomalies are commonplace among farmed fish. The pug-headedness anomaly is an osteological condition that results in the deformation of the maxilla, pre-maxilla, and infraorbital bones. Here, we report the first record of pug-headedness in an isolated population of the critically endangered native Mediterranean trout Salmo trutta L., 1758 complex from Sardinia, Italy. Fin clips were collected for the molecular analyses (D-loop, LDH-C1* locus. and 11 microsatellites). A jaw index (JI) was used to classify jaw deformities. Ratios between the values of morphometric measurements of the head and body length were calculated and plotted against values of body length to identify the ratios that best discriminated between malformed and normal trout. Haplotypes belonging to the AD lineage and the genotype LDH-C1*100/100 were observed in all samples, suggesting high genetic integrity of the population. The analysis of 11 microsatellites revealed that observed heterozygosity was similar to the expected one, suggesting the absence of inbreeding or outbreeding depression. The frequency of occurrence of pug-headedness was 12.5% (two out of 16). One specimen had a strongly blunted forehead and an abnormally short upper jaw, while another had a slightly anomaly asymmetrical jaw. Although sample size was limited, variation in environmental factors during larval development seemed to be the most likely factors to trigger the deformities.